eCM 2016
DOI: 10.22203/ecm.v032a15
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament cells as alternative source for cell-based therapy of tendon injuries: in vivo study of full-size Achilles tendon defect in a rat model

Abstract: Tendon's natural healing potential is extremely low and inefficient, with significant dysfunction and disability due to hypocellularity and hypovascularity of tendon tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…1) compared to vehicle treated ones can be interpreted as a reduction of edema and consequent scar formation. This finding is also supported by the observation that Bevacizumab treatment leads to an increase in extracellular matrix organization, a hallmark of improved tendon healing [19]. Further, to some extent, both groups showed signs of chondrification, with no detectable difference between the groups (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…1) compared to vehicle treated ones can be interpreted as a reduction of edema and consequent scar formation. This finding is also supported by the observation that Bevacizumab treatment leads to an increase in extracellular matrix organization, a hallmark of improved tendon healing [19]. Further, to some extent, both groups showed signs of chondrification, with no detectable difference between the groups (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Photomicrographs were taken on the Observer Z1 microscope equipped with the Axiocam MRm camera (Carl Zeiss). Quantitative histomorphometry was carried out via an automated quantitative image analysis according to algorithms from literature (Hsieh et al, ; Lin et al, ). In brief, using ImageJ (National Institutes of Health), the following algorithm was applied: (a) area of interest was manually designated using the “drawing/selection” tool; (b) “set measurements” for area, integrated density and mean gray value was selected from the analyze menu; and (c) lastly, the corrected total cryosections fluorescence (CTCF) representing the Acan, Col I, Col X, Fmod, Fn, Lum, MMP3, MMP‐9, p65, and Tnmd expression were exported and calculated in Excel (Microsoft) as follows CTCF = media of integrated density − (media of area of selected area × mean fluorescence).…”
Section: Methodsmentioning
confidence: 99%
“…Photomicrographs were taken on the Observer Z1 microscope equipped with the Axiocam MRm camera (Carl Zeiss). Quantitative histomorphometry was carried out via an automated quantitative image analysis according to algorithms from literature (Hsieh et al, 2016;Lin et al, 2017). In brief, using ImageJ (National Institutes of Health), the following algorithm was applied: (a) area of interest was manually designated using the "drawing/selection" tool; (b) "set measurements" for area, integrated density and mean gray value was selected from the analyze menu;…”
Section: Histology Immunohistology and Histomorphometrymentioning
confidence: 99%
“…Next day, corresponding secondary antibodies were added for 1 h. After washing, short counterstaining with 4′,6-diamidino-2-phenylindole (DAPI) (Life technology, Carlsbad, SD, USA) was performed and slides were mounted with fluoroshield (Sigma-Aldrich, Steinheim, Nordrhein-Westfalen, Germany). An automated quantitative image analysis was performed as described in Hsieh et al 2016 [9] with slight modifications. In brief, using ImageJ (National Institutes of Health, Bethesda, MD, USA), the following algorithm was applied: (1) nine images with a 40× magnification were taken per staining and cell types; (2) areas of all cells were manually designated using the “drawing/selection” tool; (3) the “set measurements” for area, integrated density and mean grey value was selected from the “analyze” menu; (4) lastly, the corrected total fluorescence (CTF) representing the expression of CD146, Nestin and STRO1 was exported and calculated in Excel (Microsoft) as follows: CTF = media of integrated density−media of the selected area x mean fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…The hTSPCs exhibit typical adult stem cell features: positivity for stem cell markers (CD73, CD90, CD105, CD146, Nestin and STRO-1), trilineage differentiation potential and expression of high levels of tendon-related genes, such as collagen type I (COL1) and collagen type III, and the proteoglycans biglycan (BGN), cartilage oligomeric matrix protein (COMP), decorin (DCN), fibromodulin (FMOD), lumican (LUM), tenascin C (TNC), and versican [6,7]. Moreover, using a full-size injury model in rat Achilles tendon, we demonstrated that hTSPCs implanted as pellets or together with carriers lead to enhanced tissue repair [8,9]. Despite their multiple benefits, the major disadvantages of autologous hTSPCs are the comorbidity and the time required for their isolation and expansion prior to use.…”
Section: Introductionmentioning
confidence: 99%